Methoxetamine‐related deaths in the UK: an overview. (July 2015) - Chiappini, Stefania; Claridge, Hugh; Corkery, John M.; Goodair, Christine; Loi, Barbara; Schifano, Fabrizio
<x xml:space="preserve">Abstract</x> Objective The goal of this study is to provide an update on the data given on methoxetamine (MXE)‐related fatalities that occurred in 2011–2013, presented at the Second International Conference on Novel Psychoactive Substances. Methods Fatalities involving MXE were extracted from the database of the National Programme on Substance Abuse Deaths, which receives information on drug‐related deaths from Coroners in the UK and Islands (Isle of Man, Jersey, Guernsey) and other data suppliers. Results Eight cases, received by 3 September 2013, in which MXE was found at post‐mortem and/or directly implicated in the death and/or mentioned in the Coroner's verdict are described. The median age at death was 27 years, with the majority of White ethnicity (6/8) and male (7/8). MXE was used together with other substances in 7/8 cases. MXE was found at post‐mortem in all cases, directly implicated in the deaths of four and likely to have had an influence in two. Conclusions More research needs to be conducted into its health effects and toxicity potential. Health care professionals should be made aware of the potential health harms of MXE, in order to develop early intervention measures and minimise the number of MXE‐related poisonings and fatalities. Copyright © 2015 John Wiley & Sons, Ltd.